2022
DOI: 10.1007/s12282-022-01408-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of home-based exercise therapy for breast cancer-related fatigue induced by radical radiotherapy

Abstract: Background Radiotherapy (RT) can lead to cancer-related fatigue (CRF) and decreased health-related quality of life (HRQoL) in breast cancer patients. The purpose of this trial was to examine the feasibility and efficacy of a home-based resistance and aerobic exercise intervention for reducing CRF and improving HRQoL in breast cancer patients during RT. Methods Women with breast cancer (N = 106) commencing RT were randomized to 12 weeks of home-based resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
0
6
0
2
Order By: Relevance
“…Two of the trials observed significant benefits of exercise (1 mixed HIIT + resistance 25 and 1 aerobic exercise 29 ) on subjective sleep outcomes (PSQI). Conversely, no statistically significant benefits of exercise on sleep were observed in the other trials 24,26,27,30,31 …”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…Two of the trials observed significant benefits of exercise (1 mixed HIIT + resistance 25 and 1 aerobic exercise 29 ) on subjective sleep outcomes (PSQI). Conversely, no statistically significant benefits of exercise on sleep were observed in the other trials 24,26,27,30,31 …”
Section: Resultsmentioning
confidence: 92%
“…One new systematic review 23 and 8 new RCTs comprising 10 intervention arms were identified 24–31 . Of the recently published RCTs, 3 focused on aerobic exercise only, 2 conducted a resistance‐only arm, 2 combined aerobic and resistance exercise, 2 used aerobic‐based high‐intensity interval training (HIIT) and 1 used a multimodal HIIT + resistance exercise intervention.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ein heimbasiertes Kraft- und Aerobic-Übungsprogramm während der Bestrahlung einer Brustkrebserkrankung (n = 106) machbar und wirksam ist, um Cancer-Related Fatigue zu lindern und die Lebensqualität zu verbessern 68 .…”
Section: Komplementärmedizinische Maßnahmen Zur Vorbeugung Und Therap...unclassified